Fluorescence angiography guided resection of small bowel neuroendocrine neoplasms with mesenteric lymph node metastases. Issue 7 (July 2021) - Kaçmaz, E.; Slooter, M.D.; Nieveen van Dijkum, E.J.M.; Tanis, P.J.; Engelsman, A.F.
Abstract: Background: Surgery for small bowel neuroendocrine neoplasms (SB-NEN) might result in vascular compromise of the remaining bowel due to resection of lymph node metastases in close proximity to main mesenteric vessels. Fluorescence angiography (FA) has been described as a safe technique to assess perfusion during gastro-intestinal surgery. This study aimed to evaluate the potential value of intraoperative FA during surgery for SB-NEN. Methods: This study included patients undergoing surgery for SB-NEN of any stage. The planned level of transection was marked by the surgeon, after which FA using indocyanine green (ICG) was performed. The primary study outcome was change in management due to FA. Results: Ten consecutive patients with SB-NEN were included, all with metastatic lymph nodes close to main mesenteric vessels. FA use led to management changes in eight patients (80%); four patients had less bowel resected with a preserved length of 5–35 cm. The other four patients had more extended bowel resections with an additional length varying from 3 to 25 cm. The median postoperative stay was 4 days (interquartile range 4–6). No anastomotic leakage occurred. Conclusion: This is the first known series describing preliminary results of FA during SB-NEN surgery. FA led to a management change in 80% of patients with better tailoring the extent of resection of small bowel. Structural implementation of FA to assess small bowel perfusion after dissection for small bowel NET results in change of management, either by preserving small bowel or resecting ill-perfused small bowel.